2019
DOI: 10.1111/apt.15397
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: risk of new onset IBD with the use of anti‐interleukin‐17 agents

Abstract: Summary Background New onset IBD has been reported with the use of anti‐IL‐17 agents, but it remains unclear to what extent this is attributed to treatment or to underlying disease. Aim To evaluate the risk of new onset IBD with the use of anti‐IL‐17 agents Methods Electronic databases were searched for randomised controlled trials (RCT) of anti‐IL‐17 agents (brodalumab, ixekizumab and secukinumab). Risk of new onset IBD was compared to placebo by Mantel‐Haenszel (MH) risk difference (RD). Sensitivity analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 92 publications
1
42
0
Order By: Relevance
“…Moreover, all IBD-related assessments were based on each physician's clinical judgement, and no specific diagnostic procedures or criteria were mandated. A similar conclusion was made by Yamada et al after a meta-analysis of 38 randomised controlled trials (RCTs) including 16,690 patients treated with anti-IL-17 agents (brodalumab, ixekizumab and secukinumab); however, as the authors stated, interpretation of the results needs caution due to the presence of many zero-event studies [30]. Other Phase 2 or 3 RCTs also did not mention new onset of IBD or IBD exacerbation among the most common side effects [31,32].…”
Section: Secukinumabsupporting
confidence: 61%
“…Moreover, all IBD-related assessments were based on each physician's clinical judgement, and no specific diagnostic procedures or criteria were mandated. A similar conclusion was made by Yamada et al after a meta-analysis of 38 randomised controlled trials (RCTs) including 16,690 patients treated with anti-IL-17 agents (brodalumab, ixekizumab and secukinumab); however, as the authors stated, interpretation of the results needs caution due to the presence of many zero-event studies [30]. Other Phase 2 or 3 RCTs also did not mention new onset of IBD or IBD exacerbation among the most common side effects [31,32].…”
Section: Secukinumabsupporting
confidence: 61%
“…No new IBD case was registered with brodalumab treatment, whereas 4 and 8 cases were reported with ixekizumab and secukinumab, respectively,. 66 In another work, one CD case was reported with brodalumab (n=1576) and 4 CD and 7 UC with ixekizumab (n=3736) for moderate-to-severe psoriasis. Ixekizumab every 2 weeks led to a moderate exacerbation of UC in one patient and new CD onset in one patient.…”
Section: Clinical Aspects Clinical Trialsmentioning
confidence: 98%
“…34 Clinical trials of anti-IL-17 therapies in rheumatology and dermatology also reported some cases of newly diagnosed IBD or IBD exacerbations. A systematic review and meta-analysis of 38 randomised clinical trials 66 evaluated the risk of new onset IBD with the use of anti-IL-17 agents (brodalumab, secukinumab and ixekizumab) in patients with psoriasis, PsA, RA and AS. In total, 12 new IBD events (5 CD and 7 UC) were found during a 60-week follow-up in the 16 690 subjects treated with anti-IL-17 drugs, corresponding to an incidence rate of 2.4 per 1000 patient-years.…”
Section: Clinical Aspects Clinical Trialsmentioning
confidence: 99%
“…As expected, an increased occurrence of candidiasis was observed in secukinumab-exposed, but not requiring the drug withdrawal, 37 while the risk of IBD development was low or absent. 38 Ixekizumab (Taltz ® ), a monoclonal antibody directed against interleukin 17A, was licensed both by EMA and FDA in August 2019 for the treatment of ankylosing spondylitis. 39,40 According to the objective of present review, the pharmacology of ixekizumab, and its efficacy and safety in the treatment of AS will be discussed in the following headings.…”
Section: Licensed Anti-il-17 Biologics For the Treatment Of Asmentioning
confidence: 99%